Anomalous X‐ray diffraction study of Pr‐substituted BaCeO3 − δ. Issue 4 (1st August 2015) - Basbus, Juan F.; Caneiro, Alberto; Suescun, Leopoldo; Lamas, Diego G.; Mogni, Liliana V.
<x xml:space="preserve">Abstract</x> The effect of Pr doping on the crystal structure and site occupancy was studied for the nominally synthesized BaCe1 − xPrxO3 − δ (x = 0, 0.2, 0.4, 0.6 and 0.8) perovskites using anomalous X‐ray powder diffraction (AXRD) data and Rietveld analysis. Crystal structure parameters were accurately determined using 10 000 eV photons, and the Pr occupancy was refined using data collected with 5962 eV photons, close to the Pr LIII absorption edge. BaCe1 − xPrxO3 − δ crystallizes in the Pnma (No. 62) space group for all x values. Pr cations are mainly located at the Ce sites (perovskites B site), but a small fraction of them increasingly substitute some of the Ba ions at the A site as Pr content increases. The Pr doping introduces electronic defects (Pr+3/Pr+4) and oxygen vacancies needed for H2O incorporation and H‐ionic conductivity. A decrease in the orthorhombic distortion would produce the opposite effects on the electronic and ionic mobility. The electronic mobility should increase due to an improvement in the overlap of the (Ce/Pr)4f–O2p orbital, while the proton mobility should decrease as a consequence of a larger hopping distance.